Investigate and Analysis of American Air Power, Upcoming Challenges and its Impact on the Territories of Influence of the Country - Aziz Nasirzadeh; Mohammad Reza Hafeznia; Ebrahim Roumina; Hossein Valivand zamani (آینده‌پژوهی دفاعی, 2022)
Since 1990, the US Air Force has continuously conducted operations in many crises in the world; On one hand, this process has caused fatigue of the current fleet of Air Force, and on the other hand, the tendency of quality human resources to serve in US Air Force has decreased, and it has prompted the commanders to overcome this problem. Modernization of air fleets with advanced "F-35" and "F-22" planes, replacement of "KC-135" and "KC-10" refuelers with "KC-46" and "B-1" and "B-2" bombers with "B-21" and with the policy of adjusting the talent of manpower, direct most of the funds towards flight projects. This article seeks to discover the challenges facing the American air power in a descriptive-analytical way and survey/field with the help of statistics and information extracted and published officially from reliable sources during 2019-2021 with Emphasis on budget programs allocated to the Air Force, as well as holding expert meetings and distributing questionnaires in an expert community in the field of aviation or a statistical community of 80 people. The results of research analysis show that the influencing factors such as: "high age and costliness of maintenance of the current fleet, projects under development, failure to provide credit on time, prolongation of the production process and ultimately failure to fulfill the plan modernizations", has placed the air force of this country in a high-stress situation and a strategic bottleneck, which, while creating ambiguous and multiple conditions, has greatly reduced the combat power of the American air force.